Development of an Early Warning System for Owners Using a Validated Health-Related Quality of Life (HRQL) Instrument for Companion Animals and Its Use in a Large Cohort of Dogs - Davies, Vinny; Scott, E. Marian; Wiseman-Orr, M. Lesley; Wright, Andrea K.; Reid, Jacqueline (Frontiers in Veterinary Science, 2020)
Preventive measures in human healthcare are recognised as a means of providing early detection of disease, however the veterinary profession has not been as effective in communicating the benefits of preventive measures to pet owners. Readily available pet healthcare information on the internet, owners not understanding that regular health evaluations can ensure the well-being of their pets and owners confusing the signs of chronic disease with normal ageing have contributed to declining numbers of veterinary visits. The use of web-based generic health – related quality of life (HRQL) measures to evaluate health status (wellness) remotely could facilitate veterinary preventive medicine. This publication describes the development and practical application of an integrated alert system for an online generic HRQL measurement instrument (VetMetrica™) which generates scores in 4 domains of HRQL - Energetic/Enthusiastic (E/E), Happy/Content (H/C, Active/Comfortable (A/C), Calm/Relaxed (C/R) - for 2 age groups (young/middle-aged, ≤7years and old, ≥8years). The alert provides an early warning, via email to owners, that a potentially significant deterioration in health status has occurred. HRQL data, collected via a white-labelled veterinary clinic branded app designed to facilitate connected care between owner and veterinarian, were analysed for 6108 dogs, ages between 6weeks and 16years. Of these 5002 were deemed to be in perfect health by their owners, yet the alert was triggered for 1343 (27%) of these, 75% of which were young/middle-aged and 25% were old, indicating that acute injuries notwithstanding, many middle-aged dogs may have been suffering from undetected chronic disease such as osteoarthritis. This work has demonstrated that the use of VetMetrica™ delivered via the PetDialog app, which supports 24/7 remote health monitoring is an efficient way for vets to provide all their owners with the opportunity to monitor their animal’s wellness throughout their lifetime, providing the vet with a mechanism to identify health problems early while stimulating owners to be more proactive in seeking veterinary attention.